2022
DOI: 10.1111/eip.13358
|View full text |Cite
|
Sign up to set email alerts
|

Help‐seeking attitudes and behaviours for mental health problems in adolescents before and during the first COVID‐19 school closures in Germany

Abstract: Aim: Comparing measures of psychological wellbeing and help-seeking in youths before and within the first school closures due to the coronavirus disease 2019 (COVID-19) pandemic enables a better understanding of the effects the pandemic has for those seeking professional help for mental health problems.Methods: Data were obtained from the Germany-based ProHEAD school study. Prelockdown and lockdown samples (n = 648) were compared regarding pupils' psychological wellbeing, help-seeking attitudes and help-seekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(16 reference statements)
0
1
1
Order By: Relevance
“…Kalok et al, measured the psychological impact of MCO towards undergraduate university students using a different measuring scale called the Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS)(9) and this could explain the difference in prevalence between our studies. In addition, the rigid safety regulations implemented during MCO from 18th March 2020 until 1st November 2021, eventually became more relaxed towards 2022(3), that may explain the lower prevalence in our study as compared to Kalok et al Several studies found psychological distress in young adults was associated with better MHSA(17,45). Although our study demonstrated psychological distress students had better MHSA than those who were non-psychologically distress, but it was not signi cant in the nal regression analysis.…”
contrasting
confidence: 53%
“…Kalok et al, measured the psychological impact of MCO towards undergraduate university students using a different measuring scale called the Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS)(9) and this could explain the difference in prevalence between our studies. In addition, the rigid safety regulations implemented during MCO from 18th March 2020 until 1st November 2021, eventually became more relaxed towards 2022(3), that may explain the lower prevalence in our study as compared to Kalok et al Several studies found psychological distress in young adults was associated with better MHSA(17,45). Although our study demonstrated psychological distress students had better MHSA than those who were non-psychologically distress, but it was not signi cant in the nal regression analysis.…”
contrasting
confidence: 53%
“…No study has shown the positive or lack of impact of the COVID-19 crisis on the general and mental health of the pediatric population [43]. The research conducted so far clearly shows an increase in the frequency of children seeking psychological support [44]. However, Boston researchers have shown that in the long run, in younger patients, the help initiative from adults is more important, and their cognitive flexibility and educational involvement lead to a reduced risk of symptoms of depression and anxiety in children [45].…”
Section: Discussionmentioning
confidence: 98%
“…During the pandemic, however any concerns they had may have continued unchecked, exacerbating these concerns and potentially experiencing loneliness more often. A previous study explored the help-seeking behaviours of CYP in relation to mental health both before and during the pandemic and suggested that those who engaged with help seeking promotion tools were perhaps more open to mental health services [31].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%